The Role of KH. Muhammad Zainuddin Abdul Majid: Improving the Education Level of the People of Lombok - Fuadul Umam Umam; Firman Firman; Baiq Madinatul Munawarah (Indonesian Journal of Social Science Education (IJSSE), 2025)
This study aims to analyse the role of KH. Zainuddin Abdul Majid in efforts to improve the education level of the people of Lombok, focusing on his contributions in the fields of religious and social education. KH Zainuddin Abdul Majid, as a prominent Islamic scholar, not only provided religious teachings but also pioneered the establishment of educational institutions that emphasised equal access to education for the community, particularly in Lombok. Through a relevant and open approach, he succeeded in introducing an education system that integrated religious values with the community's need for modern education. This study outlines various efforts made by KH. Zainuddin Abdul Majid, including the establishment of pesantren (Islamic boarding schools), providing training for educators, and his influence on the development of formal education in the region. Using a historical and qualitative approach, this research also explores the long-term impact of KH. Zainuddin Abdul Majid's influence on the social and economic transformation of the Lombok community through education.